KARAKTERISTIK IKAN HASIL TANGKAPAN ALAT TANGKAP "ILLEGAL" DI PANTAI UTARA JAWA BARAT - Wiyono, Eko Sri (Bumi Lestari, 2011)
The objectives of this study are to analyse fish catch characteristics of arad and dogol (both are likes mini trawl), which categorized as "illegal" fishing gears. Study was conducted at northern coastal of West Java province. Results of this study showed that species number and total catch weight varied among fishing gear. Based on the species number, arad which operated in Eretan Kulon could captured highest number compare to other fishing gears. On the other hand, based on the catch weight, dogol which operated in Karangreja captured highest catch weight compare to other fishing geras. The diversity analyses of catch species showed that all of fishing gears have a diversity index > 0.1. This result indicated that all of "illegal" fishing gears categorized as low species selectivity.
Keywords: arad; dogol; illegal fishing gear; diversity index